Best of the best - Surfing Australia (Sydney NSW : Hachette Australia, 2017)
From the drama of Shipsterns to the cyclonic fury of an east coast low; sunrise at Cloudbreak and rainbows at Teahupo'o, this is an awe-inspiring collection of award-winning photographs showcasing all the energy, beauty and drama of the ocean. It reveals surfers like Gilmore, Florence, Fanning and Slater in their element and the power of a moment caught in time. Featuring the winners and finalists of the Nikon/Surfing Australia Surf Photo of the Year Award from 2013 to 2017 ... these are the best of the best.'It's one thing to have an image transport you to a different place, but to actually make you feel like you're on a surfboard riding in the barrel behind one of the world's best surfers on a gnarly wave is another level of "best"!' - Stephanie Gilmore.
Contains biographical information.
Keywords: Surfing -- Australia -- Pictorial works; Surfers -- Australia -- Pictorial works; Surfer photography -- Australia; Surfers -- Australia; Australian